STRATEGY OF REGENERATION AFTER FIRE IN THE FOREST AREA OF WESTERN ALGERIA - Habib, Borsali Amine; Kheloufi, Benabdeli; Raphael, Gros (European Scientific Journal, ESJ, 2014)
The objectives of this study were of even the effects of the recurrent fires on the regeneration strategy postfire plant groupings Pinus halepensis in the Saida region (Western Algeria).Indeed, many Mediterranean species have adopted strategies of regeneration to survive fires. For that we have chosen the forest of Fenouane (Wilaya of Saïda) located in the bioclimatic floor semi arid to analyze the effect of fire on vegetation regime. This region of Algeria is marked by an important arid with higher maximum temperatures and dry a wide period this year representing a preponderant factor of the departures of fires. The results reveal a regeneration of vegetation 4 years after fire and essentially by semi mainly due to the presence in our study site of species which regenerate by seed germination. The results also show that repeated fires lead to a marked floristic depletion and burned vegetation mainly evolved maquis highlighting the intensity of the fire regime and threatening long-term pine forests. It appears from this study that fire reduces diversity and density of forest stands. The pine of Aleppo Cistus, Calycotome are mainly the only forest species that developing after fire. Resistance skills relate to their morphology and the intensity of the fire regime.